Villach – Kazan: the global trends in engineering education development - S. . Barabanova; A. . Kajbiyajnen (Высшее образование в России)
The paper deals with the problems of contemporary engineering education, which were discussed at the 41st IGIP International Conference on Engineering Pedagogy, and the 15thInternational Conference on Interactive Collaborative Learning (September 26–28, 2012 inVillach, Austria).It describes the main global and local trends in engineering education development discussed by the conference participants from 63 countries of the world. Special attention is given to global partnerships in engineering education in a number of large world class universities in the United States, Great Britain, Germany and Portugal. Successful projects ofexpress training models for engineering university faculty are analyzed.The paper dwells upon examples and methods of using interactive educational technologies for training future engineers, which were discussed in the reports of Kazan National Research Technological University professors.